2002
DOI: 10.1016/s0014-5793(02)03669-4
|View full text |Cite
|
Sign up to set email alerts
|

Integrin‐nucleated Toll‐like receptor (TLR) dimerization reveals subcellular targeting of TLRs and distinct mechanisms of TLR4 activation and signaling

Abstract: Toll-like receptors (TLRs) are activated by microbial structures. To investigate the mechanisms of TLR activation, the 10 human TLRs were expressed as chimeras with the integrin K Kv and L L5 subunits. Co-expression of the K Kv-TLR and L L5-TLR chimeras in 293T cells generated 10 TLR homodimers, but only TLR4/4 could e¡ectively activate NF-U UB. TLR4 monomers also activated NF-U UB but it was enhanced upon homodimerization. The TLR homodimers showed di¡erential surface/intracellular expression. In TLR heterodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(81 citation statements)
references
References 26 publications
2
79
0
Order By: Relevance
“…Ectodomains can be very diverse protein domains, as all of the chimeric TLR4 molecules used in this work localized to the plasma membrane, irrespective of the extracellular fusion partner used. The lack of constitutive activity of the OVA-L9-TM-TLR4 construct cannot be attributed solely to the size of OVA, as chimeras with integrins or CD4, both larger than OVA, exhibited constitutive activity in previous experiments (17,51,54). However, CD4 is an elongated molecule, and its diameter around their rotational axis at the C-terminal fusion site to the TLR4 TM segment is smaller than that of ovalbumin.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Ectodomains can be very diverse protein domains, as all of the chimeric TLR4 molecules used in this work localized to the plasma membrane, irrespective of the extracellular fusion partner used. The lack of constitutive activity of the OVA-L9-TM-TLR4 construct cannot be attributed solely to the size of OVA, as chimeras with integrins or CD4, both larger than OVA, exhibited constitutive activity in previous experiments (17,51,54). However, CD4 is an elongated molecule, and its diameter around their rotational axis at the C-terminal fusion site to the TLR4 TM segment is smaller than that of ovalbumin.…”
Section: Discussionmentioning
confidence: 90%
“…Strong dimerization of TIR domains is a unique feature of TLR4 among all the TLRs, as demonstrated by Zhang et al (51) on an example of TLR chimeras with integrins ␣ and ␤ as the fusion partners to the transmembrane and cytoplasmic domains of separate TLRs. Additionally, we have found that in contrast to TLR4, the replacement of the ectodomain of TLR3 by a small polypeptide domain does not lead to receptor activation (unpublished results) 3 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The generation of constitutively active TLR4 homodimers and TLR2 heterodimers can be achieved by the overexpression of extracellularly mutated TLR proteins or fusion proteins of intracellular TLR and extracellular integrin or CD4 domains (1,23,24), and TLR4 cross-linking can also cause signaling (25). That the elimination of the leucine-rich repeats (LRRs) that comprise much of the extracellular domain of TLR4 enables constitutive signaling suggests that the LRRs may even act to prevent multimerization of TLRs under resting conditions.…”
Section: Tlr Activationmentioning
confidence: 99%
“…Nevertheless, the role of the transmembrane domain (TMD) in TLR signaling is still elusive, while its significance for the TLR activation was demonstrated in recent studies. In particular, it was shown that constitutively dimerizing ECDs can cause the ligand-independent activation of the receptor by bringing together isolated transmembrane domain (TMD) and TIR domains [13,14]. The TLR9 receptor was shown to exist as preformed dimers in the cell membrane, while ligand binding induces only the rearrangement of the subunits [15], which seems similar to the ''coupled rotation'' activation mechanism, implying the crucial role of the receptor TMD, proposed for some receptor tyrosine kinases [16].…”
Section: Introductionmentioning
confidence: 99%